Strategies Implemented by the National System of Protected Areas of Colombia to Conserve its Paramos - Vergara-Buitrago, Paulina Alejandra (2020)
[Introduction]: Colombia has 37 paramos complexes, which constitute a strategic ecosystem for the conservation of biodiversity and ecosystem services. Thus, the development of complementary strategies for the protection of the paramos represents a mechanism to guarantee their functionality. [Objective]: To analyze the current state of articulation of the conservation strategies of the National System of Protected Areas of Colombia with the delimited paramos. [Methodology]: A review was made about the paramos complexes of Colombia, based on geographic data available in the National Registry of Protected Areas and in the Environmental Information System for Colombia. [Results]: It was found that 51.57 % of the paramos complexes are included in protected natural areas, being the category of natural national park the one that covers greater extension with 914 683.96 ha. [Conclusions]: Colombia's environmental authorities must implement conservation strategies for almost half of the country's paramo complexes, and thereby, ensure the continuity of their ecological processes and the flow of ecosystem services to the communities that inhabit them.